School Heads Digital Intelligence Quotient (DIQ), Teachers Efficacy and School Performance - Platon, Fernan L.; Astillero, Jeffrey A. (Edu Berkah Khatulistiwa, 2025)
This study explores the relationship between school heads’ Digital Intelligence Quotient (DIQ), teachers’ efficacy, and school performance in selected public elementary and high schools in Cabuyao, Laguna. As educational institutions increasingly incorporate digital technologies, it is crucial to comprehend the influence of digital leadership on the quality of instruction and overall school outcomes. The research utilized a correlational methodology to explore these connections. Information was collected from 41 participants through validated survey tools and school performance documentation, particularly the Office Performance Commitment and Review Form (OPCRF). The results indicated that school leaders showed a high level of digital intelligence, particularly in areas such as communication, leadership, and digital literacy, although they demonstrated minor weaknesses in troubleshooting and data security. Teachers also displayed strong proficiency in engaging students, implementing instructional strategies, and managing classrooms. Overall, school performance as assessed by OPCRF results was rated as very satisfactory. However, an analysis using Pearson’s correlation coefficient revealed no significant statistical relationship between the indicators of digital intelligence and teacher efficacy domains. All p-values surpassed the 0.05 threshold, suggesting that the levels of digital intelligence among school leaders do not significantly affect teachers' effectiveness in engaging students, utilizing instructional strategies, or managing classrooms. While some weak positive and negative correlations were noticed, none achieved statistical significance. Given these outcomes, a Comprehensive Digital Leadership and Instructional Improvement Program is suggested. This initiative seeks to enhance digital skills and encourage inclusive, data-informed educational practices. By equipping both school leaders and teachers with pertinent digital competencies, schools can improve collaboration, ensure equitable access, and maintain high standards of instructional quality.